Does bacille calmette-Guérin vaccination provides protection against COVID-19: A systematic review and meta-analysis - Daisy Khera; Ankita Chugh; Sameer Khasbage; Surjit Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Lower morbidity and mortality in few geographic locations on the globe suffering with SARS-CoV-2 has been associated with the existing or previously followed long-standing Bacille Calmette-Guérin (BCG) vaccination policy among infants. However, does it hold true that today after years of BCG vaccination, few adults have better prognosis or is it just confounding due to differential disease burden, population density, testing facilities, or improper reporting. The purpose was to evaluate and correlate this effect systematically. Methods: Detailed electronic search for randomized controlled trials (RCTs) and observational studies in PubMed, Cochrane Library, and ClinicalTrials.gov for eligible studies was performed. Results: One hundred and fourteen studies were yielded on search strategy and 28 observational studies were finally included for analysis. From our results, we can say that BCG vaccination causes a decrease in COVID-19 incidence and mortality. However, these results must be interpreted cautiously as lot of confounding factors were present in included studies, which can affect the outcome. Conclusion: The evidence of BCG vaccination for the protection against COVID-19 cannot be ruled out as evidence from many studies support the hypothesis, but the evidence of well-conducted RCTs and observational studies can strengthen the evidence. Registration Number: PROSPERO (International Prospective Register of Systematic Reviews) database (CRD42020204466).